PENGARUH KEGIATAN MAGANG DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA MAHASISWA STIE NUSA MEGARKENCANA YOGYAKARTA - Romadoni, Lilin Riani; Kholisoh, Luluk; Supardi, Supardi; Susilawati, Rini (Universitas Nusantara PGRI Kediri, 2023)
Students need internship activities and work motivation to mentally prepare themselves to enter the real world of work. Students who have the ability and work readiness will create a professional workforce. The purpose of this research is to find out (1) To analyze the effect of internship activities on student’s readiness to enter the world of work (2) To analyze the effect of work motivation on student’s readiness to enter the world of work (3) To analyze the effect of internship activities and work motivation on student’s work readiness. The research method used in this research is a quantitative method. The sample used in this research was students of the Accounting and Management Study Program who were or had carried out internships totaling 32 respondents. The data analysis used is multiple linear regression analysis. The results showed that: (1) The results showed that internship had a partially significant effect on the work readiness of students at the Nusa Megarkencana College of Economics, Yogyakarta, with a significance value of 0.001 < alpha 0.05. (2) The results of the study show that work motivation has a partially significant effect on the work readiness of students at the Nusa Megarkencana College of Economics, Yogyakarta, with a significance value of 0.034 < alpha 0.05. (3) . The results showed that internship activities and work motivation had a significant simultaneous effect on the work readiness of students at the Nusa Megarkencana College of Economics, Yogyakarta, with a significance value of 0.001 <0.05.